A Review of Thermal Flow Measurement Using Flow Meter - Amit Kumar,; Nilesh Vijay Sabnis, (AG Volumes, 2022)
For almost two decades, professionals have relied on Thermal Mass Flowmeters (TMFMs) for tasks as diverse as sweeping, gas injection and welding. Operators lack an adequate understanding of their operational actions. TMFMs are typically calibrated using nitrogen or air, although they may be utilised with a wide variety of process gases. Calibration using a surrogate gas necessitates the use of a correction factor (k-factor) to determine the actual flow rate of the process gas. These adjustment factors are often included in the user manual supplied by the product's manufacturer. The k-factor is crucial for accurate measurements in metrology and is used in the calibration process. Because of this, knowing whether the process gas or a surrogate gas with the suggested k-factor was utilised in calibration was crucial. The purpose of this research is to examine the implications of substituting the manufacturer's recommended k-factor for the actual process gas during calibration. This article presents test findings that are worrying in the discipline of metrology.